2006
DOI: 10.1007/s10549-006-9287-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroPET Imaging of Breast Cancer Using Radiolabeled Bombesin Analogs Targeting the Gastrin-releasing Peptide Receptor

Abstract: Mammography is a well-established method for detecting primary breast cancer; however, it has some limitations that may be overcome using nuclear imaging methods. Current radiopharmaceuticals have limited sensitivity for detecting small primary lesions and it has been suggested that novel radiopharmaceuticals are necessary for detection of primary breast cancer, as well as for detecting metastases and recurrence, or for monitoring therapy. The gastrin-releasing peptide receptor (GRPR) is a seven-transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 14 publications
(189 reference statements)
4
80
0
3
Order By: Relevance
“…Therefore the development of labeled Bn analogues for imaging or targeted cytotoxicity is a very active area of investigation at present. Numerous radiolabeled [ 111 Indium, 68 Gallium, 177 Lutetium, 64 Copper, 86 Yttrium, 18 F, 99m Tc] GRP analogues with enhanced stability that bind with high affinity to BB 2 -receptors are reported, as well as there ability to image various human tumors in vivo using gamma detectors or PET imaging [10,[69][70][71][72][73][74][75][76][77]. In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors were detected using radiolabeled Bn analogues that were not seen on other commonly used imaging modalities [75,[78][79][80].…”
Section: Iiigbb Receptors-recent Advances-tumor Imaging and Receptomentioning
confidence: 99%
“…Therefore the development of labeled Bn analogues for imaging or targeted cytotoxicity is a very active area of investigation at present. Numerous radiolabeled [ 111 Indium, 68 Gallium, 177 Lutetium, 64 Copper, 86 Yttrium, 18 F, 99m Tc] GRP analogues with enhanced stability that bind with high affinity to BB 2 -receptors are reported, as well as there ability to image various human tumors in vivo using gamma detectors or PET imaging [10,[69][70][71][72][73][74][75][76][77]. In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors were detected using radiolabeled Bn analogues that were not seen on other commonly used imaging modalities [75,[78][79][80].…”
Section: Iiigbb Receptors-recent Advances-tumor Imaging and Receptomentioning
confidence: 99%
“…They show antitumor activity in murine and human tumors (14)(15)(16). Moreover, the development of radiolabeled peptides for imaging and targeted radionuclide therapy has been advanced in recent years (17)(18)(19)(20)(21)(22)(23)(24). Clinical studies with […”
mentioning
confidence: 99%
“…At present, several GRP analogues and GRPR antagonists are in preclinical trials for tumor imaging and anticancer therapy (8)(9)(10)(11)(12)(13)(14). Although it has been reported that GRP played a role in hepatocarcinogenesis in rat (19), no data are currently available confirming the contribution of GRP to human HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, GRP serves as a potent mitogen for various types of tumor including small cell lung, pancreatic, prostate, renal, breast and colon cancers (1)(2)(3)(4)(5)(6)(7). Furthermore, treatment with GRP antibody was found to lead to significant anti-proliferative effects, indicating that GRP is an autocrine growth factor and GRPR may be a drug target for tumor imaging and anti-tumor therapy (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%